Kebenaran E-Commerce - Muhammad Mustafa Abdul Jabbar; Zainal Arif (LITERATUS, 2021)
E-commerce is an important pillar of the digital economy; Its mainly based on information technology, which is credited with creating a realistic and tangible e-commerce presence. E-commerce is one of the modern tools that has made a significant contribution to changing the future of commerce, facilitating the process of buying and selling electronically, increasing company efficiency, strengthening competitive position and marketing products electronically. The importance of research: The importance of knowing the realities of e-commerce as a cornerstone of the contemporary digital economy, as it contributes significantly to changing the future of commerce and facilitating the process of buying and selling electronically. This study aims to highlight this topic, as the number of authors is small and Arabic references are scarce. Research Methodology: This research is based on the inductive method, following the rules of scientific research and collecting scientific material from major books, with evidence, discussion and analysis.